Tata Susila Dan Pengendalian Diri Menurut Wrhaspati Tattwa - Suastini, Ni Nyoman; Wisarja, I Ketut (Jayapangus Press, 2024)
Human life is faced with behavioral problems, where humans must weigh, sort, and decide to choose these actions, and not conflict with the norms or rules that have been agreed upon and determined together by consensus. In the context of living together and socializing, self-control is very important. A person must have the ability to control himself consciously, so as to produce good behavior, not harming others, and in accordance with norms or rules, which is often referred to as “self control”. This article aims to discuss and analyze the teachings of ethics, especially morality and self-control contained in the lontar Wrhaspati Tattwa. The method used in this paper is qualitative, which focuses more on the process and meaning that is studied thoroughly, statically, and concretely in accordance with Hindu ethics and morals. This study is classified as library research which takes the main source through books, libraries, palm texts, and the internet. The results of this study are 1) Sadangga Yoga in Wrhaspati Tattwa consists of Pratyaharayoga, Dhyanayoga, Tarkayoga, Pranayamayoga, Dharanayoga, and Samadhiyoga. 2) In Wrhaspati Tattwa, morality and self-control are characterized by the Triguna nature which is part of the citta, which determines whether human life will experience good or bad. There are two factors that influence self-control and morality, namely age, which is an internal factor, and the environment, which is an external factor, both family and society. Self-control directs behavior to produce positive consequences. In conclusion, Wrhaspati Tattwa teaches that one must control the mind and heart to achieve a harmonious life.